Fast and furious: host aggression modulates behaviour of brood parasites. (23rd February 2021) - Jelínek, Václav; Šulc, Michal; Štětková, Gabriela; Honza, Marcel
Abstract : Avian brood parasites pose a serious threat to hosts, substantially reducing their fitness, which selects for the evolution of host defences. A classic example of a host frontline defence is mobbing, which frequently includes contact attacking of brood parasites. Here, we investigated how the nest defence of a very aggressive host, the Great Reed Warbler Acrocephalus arundinaceus, influences the speed of egg‐laying and egg‐removing behaviour of its brood parasite – the Common Cuckoo Cuculus canorus . We video‐recorded 168 brood parasitic events at 102 active host nests and found that Cuckoos avoided host mobbing in 62% of cases. If hosts spotted the Cuckoo at their nests, they almost always attacked it (91 of 104 cases; 88%); however, such attacks only rarely and temporarily prevented Cuckoos from parasitizing (11 additional cases). When attacked, Cuckoos parasitized host nests significantly faster and left them immediately after laying. However, when not attacked, Cuckoos frequently stayed at or near the nest, suggesting that host aggression, rather than the risk of being spotted, influences the speed of brood parasitism in this species. Further, we found that Cuckoos performed egg‐removing behaviour in all parasitic events without regard to host aggression. As a result, Cuckoos removed at least one egg during all brood parasitism events except those when the egg slipped from their beaks when they were attacked by hosts and, thus, remained in the nest (in nine of 82 cases when they were attacked; 10.9%). This indicates that egg‐removing behaviour is not costly for the Common Cuckoo and is an essential part of its parasitism strategy, widening our understanding of this elusive behaviour.